Optimization of process parameter in catalytic transesterification of biodiesel production: a comparative study / Nur Alwani Ali Bashah, Abdul Ahmad and Muhammad Hafizuddin Azman - Ali Bashah, Nur Alwani; Ahmad, Abdul; Azman, Muhammad Hafizuddin (2020)
Biodiesel is a low emission diesel substitute fuel made from renewable resources. The most common ways to produce biodiesel is by using transesterification process. The process of transesterification with the reaction of triglyceride and methanol to form the biodiesel with the aid of catalysts. The aim of this review paper is to compare the optimize reaction conditions in biodiesel production for various feedstocks and to compare the optimize of biodiesel production by using different mixed oxide catalysts. The feedstocks use in this review paper is be differentiate by two types which are edible and non-edible oil hence the comparison with biodiesel will be conducted. For the second objectives, the heterogenous catalysts are used because of their advantages that can be reused, non-corrosive and non- toxic. The heterogenous catalysts contain of two different types which are mixed oxide and mixed metal oxide catalysts. This review paper is conduct by doing a research from the previous article to analyse and get the information. The calcium oxide is the most common catalyst that use in the reaction of biodiesel. The reaction parameters used in this review paper is the reaction time, methanol: oil ratio and the reaction time. From the reaction parameters, the optimize result of biodiesel yield is be compared. The edible oil contain highest result of optimization of biodiesel compare to the nonedible. The mixed metal oxide will get better optimization compare to the mixed oxide catalyst because of the doped of metal in the mixed oxide will increase the yield of the process